Handling, sampling and stage evaluation of renal cell carcinoma: a practical guide. Issue 2 (February 2016) - Bonert, Michael; Huang, Kuo-Cheng; Trpkov, Kiril
Abstract: Tumor stage is considered the single most important prognostic factor in renal cell carcinoma. The most critical issue when determining the pathologic stage is whether the tumor is organ-confined or has spread outside of the organ and invaded the perinephric tissues and the adjacent structures. Proper handling and sampling of nephrectomy specimens is essential for accurate determination of pathologic stage and other relevant tumor parameters. Tumor staging requires careful assessment of various tumor characteristics, including tumor size, extent of tumor invasion in relation to specific kidney structures (sinus fat, renal vein and its segmental branches) and perinephric tissues (perinephric fat, Gerota fascia, adrenal gland and vena cava). Therefore, it is imperative that pathologists are familiar with the normal renal anatomy and histology, able to properly dissect surgically resected renal tumors, and able to assess specimens grossly and microscopically, to accurately determine and report pathologic stage and other relevant tumor parameters.